Cluster analysis on Malaysian student’s achievement goals orientation in mathematics from multiple goal perspective - Rustam Mohd Rameli, Mohd; Mohd Kosnin, Azlina; Kee Jiar, Yeo; Mohamad Ashari, Zakiah (International Journal of Engineering and Technology, 2018)
This study examined students’ achievement goal orientation by applying multiple goals perspective in learning Mathematics. This person-centered approach study involved 969 Malaysian upper secondary school students from 20 selected schools.  Results of correlational analysis showed that all the four goal orientations (mastery-approach, mastery-avoidance, performance-approach, and performance-avoidance) correlated moderately (r=.151-.475) to each other.  This suggests that students could adopt more than one goal orientation simultaneously.  By means of cluster analysis, the notion of simultaneous adoption of goal orientations is supported from which five distinct clusters were extracted, namely mastery-oriented (mean value is higher for the mastery-approach and mastery-avoidance goal), approach-oriented (mean value is higher for mastery and performance-avoidance goal), avoidance-oriented (mean value is higher for mastery and performance-approach goal), demotivated (low mean value for all types of goals) and success-oriented (high mean value for all types of goals).  Success-oriented cluster had the highest frequency of students (f=271, 28.0%) while only 3.6% (f=35) of the students were in the demotivated cluster.  This study extends the knowledge of how students adopt multiple goals in Mathematics learning.  The results have significant impact on mathematics education context of Malaysia.